PENERAPAN PEMBELAJARAN INOVATIF DAN INTERAKTIF PADA MATERI GEOGRAFIS INDONESIA, KERAGAMAN BUDAYA, DAN IDENTITAS DIRI SDN LIDAH WETAN IV - Manuain, Yemima (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In today's digital era, the role of technology is very important in various aspects, one of which is education. Design in learning today requires innovation in accordance with developments in time and technology. However, there are often gaps or discrepancies, namely learning is still dominated by conventional and monotonous methods.  Teachers still use lecture and storytelling methods in teaching. This results in students not being actively involved in discussions or carrying out other learning activities, thus not encouraging students to think critically and creatively. The aim of this research is to optimize the social studies and PKN learning process in elementary schools by creating innovative and interactive learning. This research uses descriptive qualitative research. The subjects of this research were teachers and students of grades 1 and 5 at SDN Lidah Wetan IV. Data collection was carried out using interviews, observation and documentation methods. The results of this research show that after carrying out innovative and creative learning at SDN Lidah Wetan IV, students can construct their own knowledge according to their abilities. Then, the use of learning media in the form of interactive power points can increase students' interest, focus and activeness during learning so that students do not feel bored. By using interactive learning media, the material presented can be understood easily by students and learning becomes more enjoyable. It can be concluded that innovative and interactive learning in elementary schools is an important thing that can be implemented to improve the quality of education. By using varied learning methods, using technology, fun learning activities, learning can become more interesting, relevant and effective.